Timed CCP compositionally embeds Argos and Lustre - Tini, Simone (Formal aspects of computing, 2004)
We prove that both the synchronous data-flow language Lustre restricted to types with finite values and the synchronous state-oriented language Argos are embedded in the synchronous paradigm Timed Concurrent Constraint Programming (tccp). In fact, for each of the two languages we provide a tccp language encoding it compositionally with respect to the syntax of programs and linearly with respect to the size of programs. Besides giving results of expressiveness for tccp, our encodings permit us to obtain a language tailored for programming reactive systems where both control handling aspects and data processing aspects are relevant.